Lyrical objects - Kilates, Marne L. (España, Manila, Philippines University of Santo Tomas Publishing House, 2015)
"Objects can assume the quality of the lyric. Only because poetry comes from the objects themselves. No ideas but in things, said the imagists. No music either. Everything breathes and vibrates in rhythm with everything. In the musica universalis, as the ancients say, or in the lay of the locality. Poetry is a natural state, a fact that the poet, often serendipitously discovers. This collection brings together 60 new poems written over three months before the poet's 60th birthday (plus some revisited and revised from previous collections), to catch up with "time's dictation" as "Dry leaves swirl in an eddy" and "The world keeps turning in a whirl." To catch up, too, with the poet's daily encounters with reality and memory that breathe, vibrate, and celebrate life in counterpoint or harmony."--Cover.
The orange parasol -- The debris -- Fish & loaves -- Dama de noche -- Lyrical objects -- Man with chessboard -- Bird of paradise -- Aubade on birdwater -- Mt. Samat war memorial -- The wars we know today -- Legazpi: Sestina of the stranger -- Memory is a ghost lurking among ruins -- (Picture of a) Rocking chair -- Puddle poem -- Hossana filio David! -- The legend of the Daraga theater -- Rubbing -- Rene, the sinapot vendor -- End of the world -- Bus ride from Argao -- Sabor a mi -- In my father's city -- Pebble poem -- Anita's women -- Monsoon ghazals Ghazal of the cadena de amor Ghazal of the kanda Ghazal of the meliguas Ghazal of the dama de noche -- Mind's pantoum -- Man sweeping leaves under the Jesuit saints of the Ateneo de Naga Church, midafteroon -- Mother's bougainvillea -- Dionysian Dionas -- Jose Rizal: my retreat -- Writingpoetry on computer -- The color of squalor -- Rosal -- Men playing pool at LMR market -- The money poem -- Old women at breakfast -- Tacada de tanaga -- Souvenir -- Remembering Russia before the fall of the wall -- Mike L. Bigornia: Only the lonely -- Poem found in Carlos Sureus' "Chinita" -- Old-fashioned windowpanes -- On a Makiling road at night -- Pilgrimage -- Adela: triolets for a violet flower -- Mangroves -- Waiting -- Monsoon Ghazals Ghazal of the camia Ghazal of the sampaguita Ghazal of the rosal Cogon ghazal Monsoon ghazal -- Gun poem -- Houses -- Secrets of the pili -- Grandmother's daud -- Entre cuatro -- Antinostalgia: the angelus (Or: under the bell) -- Under the volcano -- The legend of the Daraga republic park -- Stevedore texting -- Tacada de pinangat -- Monumento -- The book of Orag -- Jose Rizal: the traveler's song -- Translation -- Spoliarium -- The debris (2) -- Reading Wyslava Szymborska with my poetry class the day after she died -- Dry leaves swirl in an eddy (Half a sestina) -- Sitting bulul revisited -- Cherub atlas -- "Gaga over Botong" -- Crowning glory -- End of the world (2) -- Three very old pieces -- The next poem.
Keywords: Philippine poetry (English); Philippine poetry (English) -- Collections